AN ANALYSIS OF STUDENTS' DISCIPLINARY IN ENGLISH TEACHING LEARNING PROCESS AT SEVENTH GRADE OF SMP NEGERI 3 SOGAE'ADU - Lawolo, Arni Yanti; Waruwu, Yaredi; Zebua, Elwin Piarawan; Harefa, Trisman (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2025)
This study aims to analyze the level of student discipline in the English learning process and the strategies used by teachers in managing student discipline in the seventh grade at SMP Negeri 3 Sogae'adu. Student discipline issues such as lack of attention to lessons, tardiness, and lack of responsibility in completing assignments are the main focus of this study. This study uses a qualitative descriptive method with data collection techniques through observation, semi-structured interviews, and documentation. The research subjects consisted of 18 students and one English teacher. The results showed that most students had a good level of discipline, as seen from their punctuality, compliance with class rules, and responsibility and active participation in learning activities. Teachers implement three types of strategies to foster and maintain discipline, namely preventive strategies (establishing rules and positive habits), supportive strategies (giving gentle reprimands, rewards, and empathy to students), and corrective strategies (dealing with violations with a reflective and educational approach). Consistent application of these strategies, accompanied by positive relationships between teachers and students, has been shown to create a comfortable and safe learning environment that supports effective English language learning. This study concludes that student discipline is greatly influenced by teachers' humanistic and communicative strategies in classroom management, which have a direct impact on student engagement and learning achievement. ABSTRAKPenelitian ini bertujuan untuk menganalisis tingkat disiplin siswa dalam proses pembelajaran bahasa Inggris dan strategi yang digunakan oleh guru dalam mengelola disiplin siswa di kelas tujuh SMP Negeri 3 Sogae'adu. Masalah disiplin siswa seperti kurangnya perhatian terhadap pelajaran, keterlambatan, dan kurangnya tanggung jawab dalam menyelesaikan tugas menjadi fokus utama penelitian ini. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data melalui observasi, wawancara semi-terstruktur, dan dokumentasi. Subjek penelitian terdiri dari 18 siswa dan satu guru Bahasa Inggris. Hasil penelitian menunjukkan bahwa sebagian besar siswa memiliki tingkat disiplin yang baik, terlihat dari ketepatan waktu, kepatuhan terhadap aturan kelas, serta tanggung jawab dan partisipasi aktif dalam kegiatan belajar. Guru menerapkan tiga jenis strategi untuk menumbuhkan dan mempertahankan disiplin, yaitu strategi pencegahan (menetapkan aturan dan kebiasaan positif), strategi pendukung (memberikan teguran lembut, hadiah, dan empati kepada siswa), dan strategi korektif (menangani pelanggaran dengan pendekatan reflektif dan edukatif). Penerapan konsisten strategi-strategi ini, disertai dengan hubungan positif antara guru dan siswa, telah terbukti menciptakan lingkungan belajar yang nyaman dan aman yang mendukung pembelajaran bahasa Inggris yang efektif. Studi ini menyimpulkan bahwa disiplin siswa sangat dipengaruhi oleh strategi humanis dan komunikatif guru dalam manajemen kelas, yang memiliki dampak langsung pada keterlibatan siswa dan pencapaian belajar.